2017
DOI: 10.1111/cdev.12988
|View full text |Cite
|
Sign up to set email alerts
|

Seeing Iconic Gestures While Encoding Events Facilitates Children's Memory of These Events

Abstract: An experiment with 72 three-year-olds investigated whether encoding events while seeing iconic gestures boosts children's memory representation of these events. The events, shown in videos of actors moving in an unusual manner, were presented with either iconic gestures depicting how the actors performed these actions, interactive gestures, or no gesture. In a recognition memory task, children in the iconic gesture condition remembered actors and actions better than children in the control conditions. Iconic g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 44 publications
2
25
0
4
Order By: Relevance
“…A study by Cook, Yip, and Goldin‐Meadow (2010) reported positive effects of producing iconic gestures (vs. no gesture) on adult's memory representation of present events. Similar results were found by Aussems and Kita (2019) in children, showing that observing iconic gestures (vs. interactive gestures and no gesture) facilitated their recognition memory of action events. Gesturing also seems to help people generate problem‐solving strategies in mathematics (Broaders, Cook, Mitchell, & Goldin‐Meadow, 2007; Cook, Mitchell, & Goldin‐Meadow, 2008; Goldin‐Meadow, Cook, & Mitchell, 2009; Novack, Congdon, Hemani‐Lopez, & Goldin‐Meadow, 2014) and execute other thinking tasks (Alibali & Kita, 2010; Alibali, Spencer, Knox, & Kita, 2011).…”
Section: Introductionsupporting
confidence: 86%
“…A study by Cook, Yip, and Goldin‐Meadow (2010) reported positive effects of producing iconic gestures (vs. no gesture) on adult's memory representation of present events. Similar results were found by Aussems and Kita (2019) in children, showing that observing iconic gestures (vs. interactive gestures and no gesture) facilitated their recognition memory of action events. Gesturing also seems to help people generate problem‐solving strategies in mathematics (Broaders, Cook, Mitchell, & Goldin‐Meadow, 2007; Cook, Mitchell, & Goldin‐Meadow, 2008; Goldin‐Meadow, Cook, & Mitchell, 2009; Novack, Congdon, Hemani‐Lopez, & Goldin‐Meadow, 2014) and execute other thinking tasks (Alibali & Kita, 2010; Alibali, Spencer, Knox, & Kita, 2011).…”
Section: Introductionsupporting
confidence: 86%
“…Listeners are sensitive to speakers' gestures and benefit from observing these gestures during online language comprehension, encoding, and subsequent memory and learning (Holler et al, 2009;Kelly et al, 2010;Hostetter, 2011;Dargue et al, 2019). The facilitative effects of observing gestures are evidenced across children (e.g., Cook et al, 2008;Sweller, 2014, 2017;Macoun and Sweller, 2016;Vogt and Kauschke, 2017;Holler et al, 2018;Aussems and Kita, 2019;Dargue and Sweller, 2020;Kartalkanat and Göksun, 2020) and young adults (e.g., Beattie and Shovelton, 1999;Roth, 2001;Holle and Gunter, 2007;Kelly et al, 2008;Hostetter, 2011;Rueckert et al, 2017;Dargue and Sweller, 2020). Research regarding individual differences in how listeners attend to and process speakers' gestures and how much they benefit from observing gestures during comprehension and learning is quite limited, especially when compared to the literature on individual differences in gesture production (e.g., Post et al, 2013;Wu and Coulson, 2014a,b;Yeo and Tzeng, 2019;Özer and Göksun, 2020).…”
Section: Individual Differences In Gesture Processingmentioning
confidence: 99%
“…It is difficult for children to individuate the meaning of a verb (e.g., running ) in such a complex event (Gentner, 1978, 1981, 1982; Gentner & Boroditsky, 2001). This is partly because children focus on more salient components of the event, such as the person who is performing the action (e.g., the man), instead of the action itself (e.g., running; Aussems & Kita, 2017; Forbes & Farrar, 1995; Imai, Haryu, & Okada, 2005; Imai, Kita, Nagumo, & Okada, 2008; Kersten & Smith, 2002). For example, Imai et al (2008) presented 3‐year‐old children with videos of human actors moving across the length of a scene in unusual manners (e.g., walking with slow heavy steps).…”
Section: Verb Learning Is a Challenging Taskmentioning
confidence: 99%